Implementation of School Culture-Based Education in Fostering Students' Akhlakul Karimah at Al-Hananiyah Bodak Islamic Middle School 2024 - Syarifuddin, Syarifuddin; Iskandar, Muhammad Rozi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to find out how to implement school culture-based character education and what are the results of implementing school culture-based character education in developing morals? Based on the results of several studies conducted, the researchers concluded: 1. The implementation of culture-based character education at Al-Hananiyah Bodak Islamic Middle School reflects a strong commitment to the development of students' morals. Through an implementation strategy that involves the integration of cultural and religious values, the involvement of all parties, as well as supporting extracurricular activities, character education can be implemented well. The methods used, such as project-based learning, discussions, and teacher examples, further strengthen these efforts. With a holistic and comprehensive approach, Al-Hananiyah Bodak Islamic Middle School seeks to form a generation that is not only academically intelligent but also has strong character. 2. The results of the evaluation of changes in students' morals at Al-Hananiyah Bodak Islamic Middle School show positive developments. By using observation methods, questionnaires and feedback from parents, schools can assess the extent to which character values have been implemented in students' daily lives. Increasing positive behavior, awareness of responsibility, and changes in attitudes towards friends are indicators of the success of school culture-based character education. This is a motivation for all parties in the school to continue to be committed to forming a generation that has good morals.